Adaptive active noise control with genetic algorithm - Yang, Xiaoguang (2008)
The basic objective of active noise control (ANC) is to use adaptive control method to cancel the low frequency noise in different environments. It is based on the principle of superposition where a secondary anti-noise of equal amplitude and opposite phase is generated to super-impose on the primary noise.